ANALISIS PENGARUH RASIO KEUANGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN RITEL DAN FASHION DI BEI SEBELUM DAN SETELAH PANDEMI COVID 19 - Ningsih, Rani Utami (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The COVID-19 pandemic has significantly impacted the financial performance of companies, especially those in the retail and fashion sectors listed on the Indonesia Stock Exchange (IDX). Changes in consumer behavior, social order, and economic pressures have presented companies with significant challenges in maintaining profitability. This study aims to analyze the effect of financial ratios consisting of Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on the company's financial performance, which is proxied by return on equity (ROE), in the period before and after the Covid-19 pandemic (2019-2023).Methods: The research method employed is a quantitative, descriptive, and associative approach. It utilizes secondary data from the annual financial reports of 10 companies in the retail and fashion subsectors with purposive sampling techniques. After verifying the classical assumptions, the analysis was conducted using multiple linear regression.Results: The study's results show that only the activity ratio (TATO) positively and significantly affects ROE. In contrast, the liquidity ratio (CR) and solvency (DER) have a negligible impact. This study concludes that the effectiveness of asset use is a key factor in improving financial performance. At the same time, liquidity and capital structure are not the primary determinants during the post-pandemic recovery period. These findings are expected to serve as a strategic reference for management and investors in making informed financial decisions in the fashion retail sector. Keywords: Liquidity, Solvency, Activity, Financial Ratios